Posterior circulation stroke due to intracranial artery disease in the Chinese population. Issue 9 (18th August 2022) - Zhang, Changqing; Li, Zixiao; Liu, Liping; Pu, Yuehua; Zou, Xinying; Yan, Hongyi; Pan, Yuesong; Zhao, Xingquan; Wang, Yilong; Wang, Yongjun
Abstract: Background: Little is known about the distribution of the intracranial arteries that are responsible for noncardiogenic posterior circulation stroke (PCS) in the Chinese population. Furthermore, few studies have compared the imaging manifestations and outcomes across PCS due to the disease of different intracranial arteries. Therefore, our aim was to demonstrate the distribution of the intracranial arteries that were responsible for noncardiogenic PCS and to compare the imaging manifestations and outcome across PCS due to the disease of different intracranial arteries. Methods: We prospectively enrolled 690 patients from 22 Chinese centers with noncardiogenic PCS due to intracranial artery disease. Intracranial artery disease was classified as intracranial vertebral artery disease (IVAD) and intracranial nonvertebral artery disease (INVAD). Clinical‐radiologic patterns and outcomes were compared between IVAD and INVAD. Results: INVAD was more frequent than IVAD. Compared to the INVAD group, the IVAD group more frequently had hypertension, coronary heart disease, multiple infarcts, border zone infarcts, territorial infarcts, small cortical infarcts, multilevel infarcts, multisector infarcts, and more often had severe stenosis of the responsible artery, more often presented with decreased alertness, gaze palsy, bilateral limb weakness, ataxia, dysphagia, diplopia, vertigo, and headache. In addition, the IVAD group had a higher National Institutes of Health stroke scale score and modified Rankin Scale score at discharge and more deaths and recurrent ischemic cerebrovascular disease within 1 year of onset. Multivariable Cox regression identified IVAD as an independent predictor of recurrent ischemic cerebrovascular disease. Conclusions: PCS due to INVAD was more common in the Chinese population. However, PCS due to IVAD had more serious clinical‐radiologic patterns and worse outcomes. Graphical Abstract: